Comparative study between interlock nailing and dynamic compression plating in humerus diaphyseal fractures in its functional and surgical outcome - Bhavsar, Atul K.; Sharan, Sudhir M.; Shetty, Neeraj R.; Ahire, Avinash S. (International Journal of Research in Orthopaedics, 2023)
Background: The aim of the study was to analyse compare study between interlock nailing and dynamic compression plating in humerus diaphyseal fractures in its functional and surgical outcome. Methods: The 2019 to 2022, patients were randomly divided into two groups with the help of computer-generated coded envelopes, group A (humerus diaphyseal fractures treated with dynamic compression plating) and group B (humerus diaphyseal fractures treated with interlock nailing) with 20 patients in each group. Outcomes were evaluated based on operative time, blood loss, neurovascular deficit, surgical site infection, union, shoulder stiffness, constant Murley score, Mayo elbow performance index at 1 year of follow up. Results: On radiology as non-union and union, most common study participants show union, on follow up of 1 year constant Murley score and Mayo elbow performance index was calculated and constant Murley score was more in patients treated with dynamic compression plating, shoulder stiffness was more in patients treated with interlock nailing. However blood loss was more in patients treated with dynamic compression plating. Conclusions: The result of our study shows that interlock nailing is associated with less blood loss but it is associated with decreased shoulder function postoperatively and marked shoulder stiffness which is more than patients treated with dynamic compression plating. Hence dynamic compression plating should be considered gold standard for operative treatment of humerus shaft fracture.